Sources and Application Methods of Potassium Fertilizer for Cotton Cultivation in Cerrado Soil of Western Bahia - Paulo César Teixeira; Jorge Makhlouta Alonso; Lino Furia; Maria da Conceição Santana Carvalho (Revista Ceres)
ABSTRACT Potassium (K) fertilization strategies are crucial for maximizing cotton yield and fiber quality in Brazil’s Cerrado region. This study evaluated the effects of K source and application timing on cotton performance in Western Bahia. The experiment followed a randomized block design with four replications. Treatments included pre-planting applications of muriate of potash (MOP), polyhalite (Poly4), and a 50/50 MOP/Poly4 blend; post-planting (topdressing) applications of MOP and Poly4; and a control without K. Seed yield, fiber yield, fiber quality parameters, and macronutrient concentrations were assessed. Potassium fertilization significantly increased seed and fiber yields compared to the control. Among the fertilized treatments, yields and fiber quality were statistically similar. The highest leaf K concentration was observed in the post-planting Poly4 treatment, while both this treatment and the control had the highest Mg concentrations. Sulfur concentrations were higher in all fertilized treatments than in the control. Fiber quality did not differ significantly among treatments, except for the yellowing grade (+b), which was lower in the control. Additionally, cotton classification grades were higher in all fertilized treatments. These results indicate that Poly4 is a viable alternative to MOP for cotton cultivation in Western Bahia, offering additional macronutrients and flexibility in application timing.